Peace, culture, and violence - Gursozlu, Fuat. (Value Inquiry Book Series, 2018)
Peace, Culture, and Violence examines deeper sources of violence by providing a critical reflection on the forms of violence that permeate everyday life and our inability to recognize these forms of violence. Exploring the elements of culture that legitimize and normalize violence, the essays collected in this volume invite us to recognize and critically approach the violent aspects of reality we live in and encourage us to envision peaceful alternatives. Including chapters written by important scholars in the fields of Peace Studies and Social and Political Philosophy, the volume represents an endeavour to seek peace in a world deeply marred by violence. Topics include: thug culture, language, hegemony, police violence, war on drugs, war, terrorism, gender, anti-Semitism, and other topics. Contributors are: Amin Asfari, Edward Demenchonok, Andrew Fiala, William Gay, Fuat Gursozlu, Joshua M. Hall , Ron Hirschbein, Todd Jones, Sanjay Lal, Alessandro Rovati, Laleye Solomon Akinyemi, David Speetzen, and Lloyd Steffen.